Practical aspects of rape investigation : a multidisciplinary approach - Burgess, Ann Wolbert; Hazelwood, Robert R. (CRC series in practical aspects of criminal and forensic investigations, 2009)
A resource on rape investigation. It brings into focus the five different principals involved in a rape investigation: the police investigator, examining nurse, forensic scientist, crisis counselor, and prosecutor. It demonstrates how professionals can work together to effectively handle even the complex sexual assault crime